THE ROLE OF SPIRITUAL LEADERSHIP AND WORK ETHIC IN INCREASING PRODUCTIVITY - Eka Dirgantara Aquino; Multifiah Multifiah; Asfi Manzilati (Journal of Indonesian Applied Economics, 2020)
This study aims to examine the role of spiritual leadership and work ethic in increasing productivity. The research metode used in this study is a qualitative method, by employing a case study approach, data analysis used is reduction, data display end verification. The result of this study stated that spiritual leadership at BSM has a role in increasing productivity, so does the work ethich also has a role in increasing productivity. The increased productivity was indicatedÂ  by an increase in the performan of BSM Area Malang, namely the achievements of profit targets in 2019 listed in the contribution margin report and BSM Area Malang couldÂ  be the best in terms profitability among BSM in other areas